2004
DOI: 10.1038/sj.ejhg.5201245
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the PRNP gene in Chinese populations and the identification of a novel insertion mutation

Abstract: The two common polymorphisms (385A4G: M129V and 655G4A: E219 K) in the human prion gene (PRNP) play important roles in the pathogenesis of Creutzfeldt -Jakob diseases. We screened a total of 626 individuals, who represent three ethnic populations of China, Han, Hui, and Uyghur, for the two polymorphisms. The frequencies of M/M homozygote at residue 129 in these three groups differ significantly. The Han has a much higher frequency (98%) than Hui (85%) and Uyghur (60%). On the other hand, the frequencies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 20 publications
4
37
2
1
Order By: Relevance
“…The M allele frequency is highest in Central and East Asia (> 90%), high in the Pacific (approximately 81%), in Europe (57-75%) and low (approximately 30%) in Native Americans (Palmer, ApoE-4 (-) (n = 306) ApoE-4 (+) (n = 181) 1991; Soldevila et al, 2003;Jeong et al, 2004;Yu et al, 2004;Lucotte and Mercier, 2005). Similarly, the MM genotype is highly abundant (> 93%) in East Asia.…”
Section: Discussionmentioning
confidence: 99%
“…The M allele frequency is highest in Central and East Asia (> 90%), high in the Pacific (approximately 81%), in Europe (57-75%) and low (approximately 30%) in Native Americans (Palmer, ApoE-4 (-) (n = 306) ApoE-4 (+) (n = 181) 1991; Soldevila et al, 2003;Jeong et al, 2004;Yu et al, 2004;Lucotte and Mercier, 2005). Similarly, the MM genotype is highly abundant (> 93%) in East Asia.…”
Section: Discussionmentioning
confidence: 99%
“…79,80 First and foremost among these is a polymorphism at PRNP codon 129 between methionine and valine, which has a strong disease susceptibility and phenotype modifying effect. 81 There are marked differences in codon 129 allele frequency worldwide: in the UK and Northern European population, the 129M allele frequency is around 0.65 with a slightly increasing cline through Europe into Africa 79,82 and a marked increasing cline through Asia, 67,83,84 129V is rare in Japan. 129V is the more frequent PRNP allele in only two regions: the Eastern Highlands of Papua New Guinea (PNG) at 0.55, and some Native American populations.…”
Section: Prnp Polymorphisms and Prion Disease Susceptibilitymentioning
confidence: 99%
“…Small insertions have been detected incidentally or by population surveys. 67 It remains possible that small OPRI are neutral rare polymorphisms that CJD surveillance units will occasionally detect in elderly patients referred with otherwise sporadic CJD.…”
Section: Octapeptide Repeat Insertion (Opri Typically Pq75_p76ins32mentioning
confidence: 99%
“…They proposed that balancing selection played a critical role in shaping the worldwide distribution of 129V, including Fore-speaking New Guinean, African, European, and East Asian populations. In addition, it has been shown that the frequency of 129V in East Asians is low (Erginel-Unaltuna et al 2001;Jeong et al 2004;Yu et al 2004) and the Tajima's D is also lower, though positive, in East Asians than in other populations (Mead et al 2003). Kreitman and Di-Rienzo (2004) challenged the conclusions of Mead et al 2003 by pointing out that the exclusion of polymorphisms with low frequency may introduce ascertainment bias, which may tilt the estimation of the allele-frequency spectrum towards the strongly positive Tajima's D values seen in Mead's work.…”
Section: Introductionmentioning
confidence: 99%